El ejercicio del poder político en el renacimiento a través de El Príncipe - Echandi Gurdián, Marcela (2016)
In the exercise of political power during Renaissance - as well as every other time period 01' history- the social and economic context interferes, this gives place to new theories about The State and Law. The purpose of this essay is to attain the sense in which relations among The State and the citizens, The State and the Church, as well as international relations, war, natural Law, and the commercial apogee of the period are conformed.